Grande Otelo: um pícaro na cena brasileira - Silva, Camila Delfino da (2012)
This paper starts from a look over the biography and the art practiced by the actor Grande Otelo (1915-1993), and for this purpose brings data about the actor s performance at theater companies in the mid-twentieth century, as well as his experience with theater magazine, the laboratory for performance practice, as it is seen in this dissertation. His work as an actor arises from the intense relationship he kept with his public, since the moment when he used to wander through the streets reciting and performing pantomimes, until the moment of his consolidation as an actor, when he starts to perform in the theater and in the cinema. On the pathway, he developed technique for creating characters, like the scoundrel type when working in the theater magazine. In 1935, Grande Otelo had his first experience in the cinema, in the movie Noites Cariocas ; years later he made a comic couple with Oscarito, in Atlântida, a cinematographic company which brought some popularity to his career; he acted in more than 115 movies. His artistic specialization was in a genre known as slapstick comedy. Based in this term, this study enters in the general aim with more accuracy, with description and appreciation of the actor s comic performance in three movies, Matar ou correr (1954), Garota enxuta (1959) and Vai que é Mole! (1960) which bring up to date some of the constituting elements of the theater magazine and the high comedy, such as the plot, the intrigue and the resumption of the type characters. In those movies, some known personalities from that time were included, such as radio stars, since it was the most popular means of communication, in spite of the fact that some years later the cinema took its place and became the preference. Besides the update of the consulting elements of theater, there is a selection of parody speech from which arises the critique of the American domination of cinematographic business, via acting towards grotesque realism. In order to support the reading which prioritize pointing the comic recurrence found in the type characters performed by Grande Otelo, such as repetition, alogism and disguise among other features which help with the comic effect, this paper relies on studies about comicality by Henri Bergson (1980) and Vladimir Propp (1992), who systematized the cause of laughter; and in Mikhail Bakhtin (2010) about parody and its unfolding, such as carnivalization, grotesque realism and dialogue among texts which specifically trigger ambivalent laughter and propose critic sense in relation to parody movies.